PENGARUH JUMLAH BENIH PERLUBANG DAN INTERVAL PEMBERIAN PUPUK NPK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glicine Max (L.) Merrill). - Aminuddin, M. Imam (saintis, 2016)
East Java province is the hub of the soy producers in Indonesia the average dropped 1.2 tonnes/ha and the production reaches 33% of the total national production. the productivity figures are too high than the average national productivity 1.1 ton/ha. but to meet soybean self-sufficiency of 1.8 tons/ha, East Java still needs to improve the produktifitasnya of 0.6 tons/ha. This research aims to find out how big the influence range of number of seed and fertilizer NPK fertilization intervals range of Phonska against growth and production of soybean plant. This research was carried out in the village of Lebak Adi Sub Sugio, Lamongan. Height 4 meters above sea level. Research using the method of Random Design Group (RAK) factorial which is composed of two factors. Factor I namely soybean Seed perlubang (B) B1 = 1, among others, seeds per hole; B2 = 2 seeds per hole and B3 = 3 seeds per hole. While the Factor II i.e. fertilizing (F) Intervals with 3 level among other F1 = 15 days once (4 times fertilization); F2 = 20 days once (three times, fertilization); F3 = 30 days (2 times fertilization). Data observations analyzed by Fisher test (test-F) on levels 5% and 1%, if there is a real difference with Real Different trials of the smallest (Least Significant DifferenceTest) on Levels 5% Test. Research results can be concluded that 1) there is a high independent interaction on the plant, number of leaves, stem diameter, number of branches, number of flowers, number of pods, the weight of 1000 seeds dry, dry seed weight perpetak; 2) combination the best treatment on the number one seed perlubang and frequency of fertilizing four times (B1F1).